Robust Power Control for Amplify-and-Forward Relaying Scheme - Liu, Zhixin; Yuan, Huanhuan; Li, Hongxiang; Guan, Xinping; Yang, Hongjiu (IEEE communications letters, 2015)
Power control problem is investigated for amplify-and-forward cellular relay network in this letter. Since the wireless channels vary with time, we aim at a power allocation scheme that is robust to the fluctuations. An optimization problem is formulated which targets at utility maximization subject to a pre-defined outage probability threshold and limited power at relay station. With that, a distributed iterative algorithm is proposed to obtain the optimal power. Numerical results show the effectiveness of the algorithm, and also present the robustness of this system.